2020
DOI: 10.1088/2053-1591/ab6c15
|View full text |Cite
|
Sign up to set email alerts
|

UV/H2O2, UV/H2O2/SnO2 and Fe/H2O2 based advanced oxidation processes for the degradation of disperse violet 63 in aqueous medium

Abstract: The photodegradation of disperse violet 63 dye was investigated in aqueous solution using UV/H 2 O 2 , UV/H 2 O 2 /SnO 2 and Fenton reagent. The maximum decolorization was achieved in 60 min with 50 mg l −1 of dye concentration. The suitability of each process depends upon dye concentration. The photo degradation is very effective at low dye concentration. The degradation percentage increased by enhancing initial amount of hydrogen peroxide and UV irradiation time. The influence of operational parameters like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The reductions in COD, TOC and BOD values after treatment of textile real wastewater revealed that immobilized ZnO over PUF is efficient to treat the wastewater containing textile dyes, which are otherwise difficult to treat. Under the current scenario of environmental pollution [6,[14][15][16][57][58][59][60][61][62], there is need to develop and utilize efficient materials that are active under solar light and ZnO/PUF proved to be highly efficient since the activity was considerable under solar light that could possibly be used for the degradation of dyes in textile wastewater [63][64][65][66][67].…”
Section: Photocalytic Degradation Of Dyementioning
confidence: 99%
“…The reductions in COD, TOC and BOD values after treatment of textile real wastewater revealed that immobilized ZnO over PUF is efficient to treat the wastewater containing textile dyes, which are otherwise difficult to treat. Under the current scenario of environmental pollution [6,[14][15][16][57][58][59][60][61][62], there is need to develop and utilize efficient materials that are active under solar light and ZnO/PUF proved to be highly efficient since the activity was considerable under solar light that could possibly be used for the degradation of dyes in textile wastewater [63][64][65][66][67].…”
Section: Photocalytic Degradation Of Dyementioning
confidence: 99%
“…The conventional methods, including chemical methods (such as electrochemical and chemical precipitation), physical methods (such as adsorption), and biological methods are not effective in the eradication of the pesticide pollutants from the environment. Therefore, advanced methods are needed for the treatment of pesticide-contaminated water [7,15]. Techniques known as advanced oxidation processes (AOPs) are considered effective strategies for the complete remediation of the agrochemicals present in water.…”
Section: Introductionmentioning
confidence: 99%
“…That is why these techniques are getting more attraction of scientists for the removal of industrial dyes and other pollutants [13]. The formation of this oxidizing agent can be elaborated by the following equations [9,14].…”
Section: Introductionmentioning
confidence: 99%